Annual General Meeting of the Institute (The Southern African Institute of Mining and Metallurgy, 1979)
The Annual General Meeting of the South African Institute of Mining and Metallurgy was held in Kelvin House on Wednesday, 23rd August, 1978. Mr P. A. von Wielligh (President) was in the chair and declared the meeting open at 16h00. Obituaries The President: It is my sad duty to announce the death of the following members of the Institute : T. K. Prentice and W. E. Gooday, Honorary Life Fellows and Past Presidents; B. S. Allen, J. A. Becking, L. H. Mellor, C. A. Pratt and W. T. Stobart, Life Fellows; J. P. Burls, E. Cameron, M. L. Fitzgerald, C. G. Hinds, A. J. Patrick, H. O. Reisener, N. D. Shuttleworth, N. Soldan and J. Whitehouse, Fellows; T. Gemmell, J. S. A. Oelofse, W. D. Rowe, R. L. J. Shearman and G. M. Thain, Associates. As a mark of respect to the memory of the deceased and in sympathy with the bereaved, I ask you to rise and observe a few moments' silence. Welcome The President: It is now my very pleasant duty to welcome our distinguished guests and visitors. We are pleased to have with us Mr D. A. Etheredge, Vice¬President of the Chamber of Mines of South Africa, and Mrs Etheredge. Mr Etheredge this afternoon represents the mining industry at our meeting. The importance of the close link that over the years has been maintained between the industry and our Institute speaks for itself. We are, therefore, grateful that he and Mrs Etheredge have managed to find the time to be with us this after¬noon.